Pengaruh Efisiensi Kerja Pegawai Dan Standar Operasional Prosedur (SOP) Terhadap Kualitas Pelayanan Publik Pada Masa Pandemi Covid-19: Studi Kasus Di Instansi Lingkungan Kecamatan Lubuk Sikarah Kota Solok - Africha Anggraini; Rasidah Nasrah; Afni Yeni (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This research was conducted on employees at the Environmental Agency, Lubuk Sikarah District, Solok City. The purpose of this research was to find out how much influence Employee Work Efficiency and Standard Operating Procedures have on the Quality of Public Services. In this study, the population is 65 employees. With this type of quantitative research and sampling techniques using total sampling method. Data collection technique used is to use a questionnaire / questionnaire. Based on multiple linear regression analysis, of the Employee Work Efficiency variable and Standard Operating Procedures affect the Quality of Public Services Y = 21.179 + 0.367X1 + 0.336X2+ e. From the t test conducted, it was found that the Employee Work Efficiency variable had a significant effect on Service Quality with t count 2.711 > t table 1.999 and a significant level value of 0.009 <α 0.05, then H0 was rejected and H1 was accepted. It is known that the Standard Operating Procedure variable on Service Quality has tcount 2.084 > ttable 1.999 and sig 0.041 <0.05. Then Ha is accepted and H0 is rejected. From the F test it is known that fcount is 5.518 > ftable 3.15 and has a significance (0.006 <0.05). Then Ha is accepted and H0 is rejected. From the Determination Test, the R square value is 0.389 or 38.9%. This indicates that the contribution of the Employee Work Efficiency and Standard Operating Procedures variable is 38.9%. While the remaining 61.1% is influenced by other variables.